ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN J&T EXPRESS DI KOTA BENGKULU - Selvi Maharani; Sri Ekowati (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
This study aims to determine the Analysis of the Effect of Service Quality on Customer Satisfaction at J&T Express Companies in Bengkulu City. This research uses quantitative descriptive research. With the number of samples in this study as many as 80 people. Methods of data collection using a questionnaire. With data analysis techniques using a simple linear regression analysis test, the coefficient of determination (R2) and hypothesis testing, namely the t test. The results of this study can be concluded that the service quality variable has a positive and significant effect on customer satisfaction at J&T Express companies in Bengkulu City. This means that if the quality of service increases, customer satisfaction will also increase. Based on the test results of simple linear regression analysis, the formulation Y = 17.047 + 0.175 (X) was obtained. coefficient of determination R2 = 0.067 or 6.7% while the rest is influenced by other variables not examined in this study. And the results of the t test hypothesis variable service quality (X) with a significance level of 95% (Î± = 0.05). Significance figure (P Value) of 0.011 <0.05. Keywords: Quality of service, Customer Satisfaction